LONG-TERM RESULTS OF EXTREMITY SOFT TISSUE SARCOMAS LIMB-SPARING SURGERY AND RADIOTHERAPY - Dogan, Ozlem Yetmen; Oksuz, Didem Colpan; Atalar, Banu; Dincbas, Fazilet Oner (ATHA COMUNICACAO \& EDITORA, 2019)
Objective: To assess the prognostic factors and results of limb sparing surgery and postoperative radiotherapy (PORT) in patients with non-metastatic soft tissue sarcomas (STS) of the extremities. Methods: Between 1980-2007, 114 extremity-located STS treated with PORT were analyzed retrospectively. Tumors were mostly localized in the lower extremities (71,9\%). The median radiotherapy (RT) dose was 60.9 Gy. Chemotherapy was administered to 37.7\% of the patients. Tumor sizes were between 3-26 cm (median 7 cm). The three most frequent histological types included undifferentiated pleomorphic sarcoma (26.3\%), liposarcoma (25.4\%), and synovial sarcoma (13.2\%). The median follow-up for all patients was 60 months, and 81 months for survivors. Results: The 5- and 10-year local control (LC) rates were 77\% and 70.4\%, respectively

actuarial survival rates for 5 and 10 years were 71.8\% and 69.1\%, respectively. Increasing the dose above 60 Gy for all patients and the patients with positive margins demonstrated a clear benefit on 5-year LC (p =0.03 and p=0.04, respectively). Based on multivariate analysis, the addition of chemotherapy and RT dose were independent prognostic factors for LC. A recurrent presentation significantly affects the disease-free survival. Conclusions: PORT for STS of the extremities provides good long-term disease control with acceptable toxicity in a multidisciplinary approach.
Keywords: Soft tissue sarcomas; Extremities; Radiotherapy